Psychological perspectives on online transactional collaborative learning: A qualitative analysis of lecturers' and undergraduates' experiences in higher education - Dian Veronika Sakti Kaloeti; Kurniawan Teguh Martono (Insight: Jurnal Ilmiah Psikologi, 2025)
This study explores how lecturers and undergraduates perceive, experience, and navigate psychological engagement, motivation, and cognitive load online Transactional Collaborative Learning (TCL), highlighting its benefits, challenges, and psychological impact on student learning experiences in higher education. The study used Focus Group Discussion (FGD) as a qualitative research method that facilitates in-depth exploration of participants’ experiences, perceptions, and attitudes regarding a particular phenomenon. The participants in this research were ten lecturers and twenty-four undergraduate students selected purposively. The study focuses on how the online TCL environment affects psychological variables related to teaching and learning.  From the results of the thematic analysis, four final themes were obtained, including 1) learning models and strategies in online TCL; 2) effective learning models in online TCL; 3) factors influencing the success of online TCL; 4) psychological impacts of online TCL. Findings show that flexible content delivery, interactive discussions, and quizzes enhance student engagement, knowledge retention, and digital literacy. However, challenges such as technological limitations and the lack of guidance and support from lecturers hinder the success of online TCL. While this approach fosters motivation, self-confidence, and adaptability, cognitive load remains a concern. Strengthening digital infrastructure and interactive teaching strategies is key to optimizing online TCL. The implication of the study is further discussed. Keywords: Cognitive load, lectures, motivation, online transactional collaborative learning, psychological engagement undergraduate students